PENGARUH KEBERHASILAN INSEMINASI BUATAN (IB) ANTARA SAPI BALI DARA DENGAN SAPI BALI YANG PERNAH BERANAK DI KECAMATAN PEMAYUNG KABUPATEN BATANGHARI - Fachroerrozi Hoesni (Universitas Batanghari Jambi, 2015)
The purpose of this research is to know the comparative success of artificial insemination (IB) between the Wallaby dara with Wallaby ever litter is in district Pemayung District Batanghari.The method used is the method surve. Data retrieval is done by noting the central services directly from artificial insemination Pemayung Sub District Batanghari. Livestock which sample is 15% of acceptors artificial insemination beef cattle with dara Bali Bali beraanak ever. Determination of sampling was done randomly (Simple Random Sampling).Data collected processed in descriptive and analyzed using Chi Square test and test t. To know the link between number of insemination should be done for every marital status kebuntingan, and the success of the kebuntingan one kaliu artificial insemination based on marital status, as well as the calculation of the number of service per consepsi.Based on the research results obtained in comparison to the fact that Conception Rate (CR) and Service per Consepsi (S/C) for beef and cattle ever dara increased and each is 45%; 48.88% and 2.22; 2.04. In addition, the results of the study also showed the absence of differences, the number of insemination should be done to produce a kebuntingan good on beef as well as beef ever dara litter (P > 0.05). Similarly, the success of the kebuntingan one time artificial insemination because it proved there is no entanglement result kebuntingan one time artificial insemination with marital status (p. > 0.05).Research results can be concluded that there is no difference between artificial insemination success Wallaby dara with Wallaby ever litter, reviewed the amount of the insemination must be made for each kebuntingan and kebuntingan success one time artificial insemination.Keywords: insemination, service per consepsi (S/C)